2012
DOI: 10.1111/j.1442-2050.2012.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year experience of esophageal self-expanding metal stent insertion at a single institution

Abstract: Palliation of malignant dysphagia can be achieved using self-expanding metal stents (SEMS). This study was conceived to confirm that the insertion of SEMS improved patient symptoms without serious complications and to allow comparison with recent national data. Retrospective case note review of all patients receiving SEMS over a 10-year period between March 1999 and February 2009 was used in this study. There were 138 consecutive patients (50 female), median age of 75 (range 46-90) years, 122 (88.5%) had prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
(49 reference statements)
1
10
2
Order By: Relevance
“…Previous studies have reported that the occurrence of adverse events in SEMS insertion was 36-50%. 11,12 Adverse events occurred in 22.9% of patients in the present study and developed less frequently than was found in other studies. Most of the adverse events were not lethal and more than 70% of them were managed with an additional endoscopic procedure.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous studies have reported that the occurrence of adverse events in SEMS insertion was 36-50%. 11,12 Adverse events occurred in 22.9% of patients in the present study and developed less frequently than was found in other studies. Most of the adverse events were not lethal and more than 70% of them were managed with an additional endoscopic procedure.…”
Section: Discussioncontrasting
confidence: 44%
“…Covered self-expandable metal stents are often used for this indication, and their use is associated with marked improvement in dysphagia symptoms. 160, 161 However, this therapy has not been shown to increase survival times, and patients and clinicians must be familiar with the potential side effects of stent placement. One common side effect is stent migration, which occurs in up to 15% of patients and can require surgery for removal.…”
Section: Treatmentmentioning
confidence: 99%
“…In the late term after stenting, food bolus impaction is reported to occur for 7% in the literature. 46 We encountered food bolus impaction in one of our patients (1.4%) who was using dentures because of chewing disfunction and dysphagia in 6 patients (8.7%) caused by tumor overgrowth. These rates are about 12.3% in the literature.…”
Section: Discussionmentioning
confidence: 80%